A Numerical Study On Behavior Characteristics Of Steel-Concrete Composite Drilled Shafts - Hyu-Soung Shin (Deep Foundations Institute, 2007)
This study is concerned with the characteristics of the behavior of steel-concrete composite drilled shafts, a material that is used for large bridge foundations, and especially for weak submerged ground conditions. Depending on the loading or boundary conditions considered, the behavior of foundation will vary. The bearing capacity of steel-concrete composite drilled shaft is influenced by initiation and propagation of fractures along the interface between steel casing and filled concrete. The interface effect is taken into account with the following two simplified cases: (1) detached model with free interface (no shear stiffness of interface) between concrete core and steel casing, (2) confined model by an upper steel cap with free interface. In the confined model, it is intended to have an unified behavior of composite shaft between concrete core and steel casing but there is interface between them. Intensive numerical studies have been undertaken to investigate detailed behavior of the composite shaft. In this study, 3-D finite element analysis is employed. Ground conditions typical of those encountered for the design of drilled shaft under water are considered affecting the behavior. Also, an attempt is made to generate possible combinations of the loads which have been considered in fields. Detailed characteristics of the stress and displacement distributions are evaluated to understand the mechanisms of composite shafts.